A contextual learning model for developing interactive e-books to improve students' performances of learning the Analects of Confucius. Issue 3 (17th February 2022) - Sung, Han-Yu; Hwang, Gwo-Jen; Chen, Chin-Yu; Liu, Wen-Xiu
ABSTRACT: The Analects of Confucius has been identified as an important and influential philosophy around the globe. However, in traditional instruction, it is difficult to express the spirit of this philosophy. Therefore, many students consider it as a big challenge to study the Analects of Confucius. To cope with this problem, in this study, an interactive e-book system has been developed based on the contextual learning model to interpret the Analects of Confucius in an interactive way. A quasi-experiment was conducted to evaluate the performance of the proposed approach. The participants were 38 fifth graders from 2 classes in an elementary school located in northern Taiwan, who were divided into an experimental and a control group. The experimental group used an interactive e-book learning mode to learn the Analects of Confucius course while the control group used a conventional technology enhanced teaching mode. The results showed that adopting the interactive e-book teaching mode to study the Analects of Confucius in the elementary school course can promote students' learning achievement and motive. It was also found that the interactive e-book learning mode can trigger learners' deep motive, and hence promote their learning achievement.